Penggunaan inovasi teknologi komunikasi dalam pengembangan pertanian di Lembaga Kemajuan Pertanian Muda (MADA) - Ahmad Fahmi, Mahamood (2018)
This study discusses on the use of communication technology innovation in the development of agriculture. Communication technology is refer to an advanced innovation that has to be fully utilized by the farmers as it is the means to get hold of various agricultural information to help improve of their quality of agricultural efforts. Most farmers are merely way behind in terms of utilizing the innovation communication technology, which has prompted the researchers to scrutinize this issue in greater depth. Based on the Diffusion of Innovation Theory, and the Unified Theory of Acceptance and Use of Technology (UTAUT), this study observed the effectiveness of the combination of these two theories and the roles of the extension agents in the use of communication technology innovation among farmers. This study combined both the quantitative method through the use of questionnaires and a focused group as the qualitative method. 398 farmers were chosen as respondents. In addition, a focused group discussion involving ten farmers was conducted to support the findings of the quantitative data. Descriptive and inferential tests were carried out on the quantitative data. Meanwhile, thematic analysis was employed to analyse qualitative data. The result showed there is a significant relationship between the characteristics of innovation and technology acceptance. The influence of the characteristics of innovation, which are the relative advantage and the observability on technology acceptance, is at 10.2% of variance changes. Discriminant analysis found that there is a significant difference in farmers' locality in accepting technology. The qualitative findings showed that the role of the extension agents has to be increased in order to inspire the farmers to use the innovation. This study developed a model that integrates both theories, the role of the extension agent and locality in understanding the issue of communication technology innovation usage among the farmers. This model can be further improved or modified for future research to identify other factors that could play a role in the use of this innovation.